EFL Teachers' and Students' Attitudes and Practices Regarding Oral Communication in English Classes: Ethiopian High School Context - Eyasu Yaya Sada; Dereje Asfaw Bulbula; Tesfa Alemu Bulti (International Journal of Language Education, 2023)
This study looked at the attitudes of Ethiopian English teachers and Bonga Mehal Ketema High School grade 10 students about spoken communication in the classroom. The purpose of this study was to determine why oral communication is such an important part of English teaching, what role teachers and students play in making orally active students in the English classroom.  Four English teachers were purposively interviewed, and 95 pupils in the tenth grade completed a questionnaire. The findings show that the majority of teachers and students believe that oral communication is an important aspect of the English education process. It is primarily due to the fact that being able to express yourself vocally in English in today's world is extremely important. The findings also reveal that teachers believe assessing students' oral competence is difficult since it is not as concrete as other abilities assessed in the English foreign language course. The challenge of convincing timid or unmotivated students to engage orally, as well as a lack of time, make assessing students a challenging undertaking. Thus, EFL teachers should establish a welcoming environment in the classroom to help students enhance their speaking skills.